2005
DOI: 10.1097/01.ju.0000162056.30326.83
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss: A Novel and Effective Treatment for Urinary Incontinence

Abstract: Purpose-We evaluated the effect of weight loss on urinary incontinence (UI) in overweight and obese women.Materials and Methods-A randomized, controlled clinical trial was conducted among overweight and obese women experiencing at least 4 UI episodes per week. Women were randomly assigned to a 3-month liquid diet weight reduction program (24 in the immediate intervention group) or a wait-list delayed intervention group (24 in the wait-list control group). Participants in the waitlist control group began the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
165
3
24

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(198 citation statements)
references
References 15 publications
(3 reference statements)
6
165
3
24
Order By: Relevance
“…Further, intentional weight loss has been shown to result in improvement or remission of incontinence, 17 but loss of 10 pounds in the past year was not protective of developing new incontinence in our study. Future studies of intentional weight loss should include older participants and add incontinence as an endpoint to determine if regaining continence could be an additional health benefit of successful dieting in older as well as younger persons.…”
Section: Discussioncontrasting
confidence: 83%
“…Further, intentional weight loss has been shown to result in improvement or remission of incontinence, 17 but loss of 10 pounds in the past year was not protective of developing new incontinence in our study. Future studies of intentional weight loss should include older participants and add incontinence as an endpoint to determine if regaining continence could be an additional health benefit of successful dieting in older as well as younger persons.…”
Section: Discussioncontrasting
confidence: 83%
“…Most of these studies were in overweight or obese women [19][20][21][22] and have found that weight loss resulted in significant improvement in continence. There was a suggestion of an increase in the odds of urinary incontinence in the women who have lost weight compared with those who have maintained a BMI below 25 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…11 Studies that have identified a relationship between higher body weight in midlife and incontinence have been either cross-sectional [12][13][14][15][16][17][18] or short-term studies. [19][20][21][22] Obesity, particularly in the abdominal area, may cause incontinence through increased intra-abdominal pressure. 23,24 Given rising childhood and adolescent obesity, 25 and as high body mass index (BMI) is likely to persist over the life course, important questions remain regarding the influence of weight trajectories, in terms of the duration or timing of overweight/obese status, on urinary incontinence.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 A randomized study showed that weight loss is associated with decrease in the prevalence of UI. 40 A study conducted in the state of Washington, USA, interviewed women between 30 and 90 years and showed that the variable BMI > 30 kg m 2 doubled the risk of developing UI. 41 Tennstedt et al believe that the ratio between abdominal circumference and pelvic circumference is a better predictor than BMI because it indirectly measures the intra-abdominal pressure that affects the pelvic floor and elevates the intravesical pressure.…”
Section: Discussionmentioning
confidence: 99%
“…5 Fultz et al assessed the impact of UI in 3,364 employed women and demonstrated impairment of work rhythm because of increased frequency of bathroom breaks. 6 Tamanini et al, using the International Consultation on Incontinence Questionnaire (ICIQ-SF), showed that among 225 patients with UI, 8.9% (20) and 17.8% (40) considered the impact of this condition on their quality of life to be severe and very severe, respectively. 7 Telephone interviews conducted in 2003 with 82,196 people over 65 years demonstrated that the prevalence of UI is twice as high in women compared to men and UI is significantly associated with depression.…”
Section: Introductionmentioning
confidence: 99%